Combined solvent and vapor treatment to prepare high quality perovskite films under high relative humidity. (20th August 2017) - Cheng, Nian; Li, Weiwei; Yu, Zhenhua; Wang, Changlei; Qi, Fei; Liu, Pei; Xiao, Yuqing; Zhao, Xing-Zhong
Highlights: A facile method is proposed to prepare high quality perovskite films. Perovskite film with micrometer scaled particles is obtained. The quality of the perovskite films is confirmed in HTM free PSCs. Champion PCE of 16.61% is obtained. Abstract: It is a great challenge to prepare high quality perovskite films in ambient atmosphere with high humidity (≥ 50%), since the commonly adopted two step sequential deposition process produces perovskite films with rough surfaces and a large amount of residual PbI2 . To solve these problems, a facile method using combined solvent and vapor treatment is proposed. The residual PbI2 is diminished through a solvent treatment process, and then smooth perovskite surface with micrometer scaled perovskite particles is obtained with a CH3 NH2 vapor treatment. The quality of the obtained perovskite films is examined in the hole transport material free perovskite solar cells, and power conversion efficiency is boosted up by 17.3% compared with the traditional method. When a CuPc hole transport layer is further introduced, carbon counter electrode based perovskite solar cells exhibit a superior power conversion efficiency of 16.61%. Thus this method shows great potential in further optimizing the performance of perovskite solar cells.